National Geographic atlas of the world - National Geographic Society (United States of America : National Geographic Society, 1990)
I believe that the atlas is one of e most valuable tools in the Society's phic literacy.
Contents 1. Dynamic earth 2. Continents adrift 3. Tectonic earth 4. Earth's crust 5. Habitable earth y otros sesenta y tres más....
incluye abbreviations, map symbols, mejor cities of the united states, major cities of the world, index
Contiene preface, foreword, contents
Keywords: GEOGRAFIA -- MAPAS